(untitled) (LEGAL DIALOGICA, 2025)
This research examines the Legal Review of Standard Clauses Made by Mall Management for Parking Facilities in Makassar City. This writing uses a Normative legal research method sourced from primary legal materials and secondary legal materials, primary legal materials are legal materials sourced from the Holy Book and legal materials sourced from statutory regulations, and also legal materials that have general binding force and secondary legal materials are various references or scientific works in the field of law, in the form of law books, legal articles, legal journals, inaugural speeches for professors in law, scientific oration manuscripts in the field of law and academic manuscripts in the field of law, legal manuscripts resulting from workshops and so on. The results of this paper indicate that the legal provisions governing the use of standard clauses in privately managed parking facilities are Article 18 of the Consumer Protection Law, which prohibits businesses from including standard clauses in agreements that transfer their responsibilities. Article 7 of the Consumer Protection Law, which provides compensation or redress to consumers if a business fails to fulfill its obligations. Furthermore, regarding consumer legal protection against standard clauses on parking tickets, the state has provided protection for consumers against the use of standard clauses on parking tickets. This can be found in Article 19 of the Consumer Protection Law concerning the responsibilities and forms of compensation provided by businesses for losses suffered by consumers, one of which is losses resulting from standard clauses included in parking tickets. Recommendations for this paper: (1) Parking management does not need to include clauses stating the transfer of responsibility. (2) Consumers, as users of parking services, are required to understand their rights and obligations before using goods and/or services. Abstrak: Penelitian ini mengkaji tentang Tinjauan Hukum Terhadap Klausula Baku yang di Buat Oleh Pihak Pengelola Mall Untuk Fasilitas Ruang Parkir di Kota Makassar. Penulisan ini menggunakan metode penelitian hukum Normatif yang bersumber dari bahan hukum primer dan bahan hukum sekunder, bahan hukum primer yaitu bahan hukum yang bersumber dari Kitab Suci maupun bahan hukum yang bersumber dari peraturan perundang-undangan, dan juga bahan hukum yang mempunyai kekuatan mengikat secara umum dan bahan hukum sekunder yaitu berbagai referensi atau karya-karya ilmiah bidang hukum, berupa buku hukum, artikel hukum, jurnal hukum, naskah pidato pengukuhan guru besar bidang hukum, naskah orasi ilmiah bidang hukum dan naskah-naskah akademik bidang hukum, naskah hukum hasil lokakarya dan sebagainya. Hasil penulisan menunjukkan bahwa Pengaturan hukum terhadap penggunaan klausula baku pada fasilitas ruang parkir yang dikelola oleh pihak swasta yaitu Pasal 18 Undang-undang Perlindungan Konsumen yang berkaitan dengan larangan pelaku usaha untuk mencantumkan klausula baku dalam perjanjian yang sifatnya mengalihkan tanggung jawab pelaku usaha. Pasal 7 Undang-undang Perlindungan Konsumen yang berkaitan dengan pemberian kompensasi atau ganti kerugian kepada konsumen apabila pelaku usaha lalai dalam kewajibannya. Dan Perlindungan hukum konsumen terhadap klausula baku pada karcis parkir yaitu negara telah melakukan perlindungan terhadap konsumen terhadap adanya klasula baku pada karcis parkir. Hal tersebut dapat ditemukan pada UUPK Pasal 19 mengenai tanggung jawab dan bentuk ganti rugi oleh pelaku usaha akibat adanya kerugian terhadap konsumen, salah satunya adalah kerugian akibat klausula baku yang dicantumkan pada karcis parkir. Rekomendasi penulisan : (1) Pihak pengelola parkir tidak perlu mencantumkan klausula-klausula yang menyatakan pengalihan tanggung jawab. (2) Konsumen sebagai pengguna jasa parkir dituntut untuk memahami hak dan kewajibannya sebelum memanfaatkan barang dan/atau jasa.